1970
DOI: 10.1039/j29700001334
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the tautomers of adenine

Abstract: The electric dipole moments and the U.V. absorption spectra of some adenine derivatives were measured, In agreement with theoretical predictions, the moments of the N ( 7 ) H tautomer derivatives were found to be by several debyes higher than those of the derivatives of the N ( 9 ) H and N ( 3 ) H tautomers. The N ( 3 ) H tautomer of adenine is possibly a mixture of the amine and the imine forms, while the N (7) H and N (9) H tautomers exist wholly in the amine form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…5 The first experimental investigation of aminoimino tautomerism of adenine was performed in 1970. 6 The obtained results were in agreement with previous theoretical predictions formulated by Pullman et al 7 Modern computing methods and experimental techniques allow one to elucidate the molecular structure in greater detail and to perform a deeper analysis of tautomeric mixtures. Recently 23 prototropic tautomers (nine amino and fourteen imino forms) were investigated.…”
Section: Introductionsupporting
confidence: 89%
“…5 The first experimental investigation of aminoimino tautomerism of adenine was performed in 1970. 6 The obtained results were in agreement with previous theoretical predictions formulated by Pullman et al 7 Modern computing methods and experimental techniques allow one to elucidate the molecular structure in greater detail and to perform a deeper analysis of tautomeric mixtures. Recently 23 prototropic tautomers (nine amino and fourteen imino forms) were investigated.…”
Section: Introductionsupporting
confidence: 89%
“…A comparison of the experimental dipole moments of methyl and benzyl adenine derivatives, measured in dioxane, with calculated dipole moments indicates that the most stable tautomer of adenine is the N(9)H form. 35 In NMR studies of adenine in Me2SO it is found that adenine exists in an amino N(9)H structure. 36 Results of magnetic circular dichromism studies of adenine,12 the N(9)H and N(7)H tautomers occur in approximately equal quantities.…”
Section: Resultsmentioning
confidence: 99%
“…This dependence on solvent polarity has been explained by the 7-H tautomer having a substantially larger dipole moment than the 9-H tautomer. 19,44 Naturally, the amount of published material is less exhaustive for 2-aminopurine. Very recent calculations show that the 9-H tautomer has about 18 kJ/mol lower enthalpy of formation than the 7-H tautomer of 2-aminopurine in the gas phase.…”
Section: Discussionmentioning
confidence: 99%